2019
DOI: 10.1186/s12933-019-0876-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute hyperglycemia on layer-specific left ventricular strain in asymptomatic diabetic patients: an analysis based on two-dimensional speckle tracking echocardiography

Abstract: Background Hyperglycemia has detrimental effect on ischemic myocardium, but the impact of acute hyperglycemia on the myocardium in asymptomatic diabetic patients has not been fully elucidated. Thus, this follow-up study was aimed to investigate the effects and reversibility of acute hyperglycemia on regional contractile function of left ventricle (LV) in diabetic patients without cardiovascular disease. Methods The two-dimensional speckle tracking echocardiography (2D-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
3
20
0
1
Order By: Relevance
“…In addition, studies in hypertension have found that GCPS was significantly reduced in patients with hypertrophy [17,23]. Recent studies showed the negative effects of acute hyperglycemia on systolic LV global longitudinal strain and multilayer longitudinal and circumferential strain in asymptomatic T2DM and unfavorable subclinical reductions in global and average circumferential strain in obese adolescents with dysglycemia, which may indicate the importance of intensive blood glucose control [24,25]. Moreover, epicardial adipose tissue may be associated with LV structural and functional abnormalities and exercise intolerance in T2DM patients with asymptomatic heart failure [26], and serum levels of omentin-1 and Zinc-α2-glycoprotein have been recently defined as the most important predictors for LV hypertrophy and LV diastolic dysfunction in T2DM patients [27].…”
Section: Table 4 Multivariable Association Of Diabetes With First-pasmentioning
confidence: 99%
“…In addition, studies in hypertension have found that GCPS was significantly reduced in patients with hypertrophy [17,23]. Recent studies showed the negative effects of acute hyperglycemia on systolic LV global longitudinal strain and multilayer longitudinal and circumferential strain in asymptomatic T2DM and unfavorable subclinical reductions in global and average circumferential strain in obese adolescents with dysglycemia, which may indicate the importance of intensive blood glucose control [24,25]. Moreover, epicardial adipose tissue may be associated with LV structural and functional abnormalities and exercise intolerance in T2DM patients with asymptomatic heart failure [26], and serum levels of omentin-1 and Zinc-α2-glycoprotein have been recently defined as the most important predictors for LV hypertrophy and LV diastolic dysfunction in T2DM patients [27].…”
Section: Table 4 Multivariable Association Of Diabetes With First-pasmentioning
confidence: 99%
“…Subclinical systolic dysfunction was predominantly assessed using 2D STE parameters: GLS was measured in most of the cases, but global circumferential (GCS) and radial (GRS) strains were also measured in some of the included studies 4,7,8,16,21‐25 (Table 1). Furthermore, few studies also used 3D STE 1,7,26 and multiple‐layer strain 5,8,21,27‐30 for systolic function assessment. Systolic dysfunction was correlated with lower absolute values of GLS, GCS or GRS, 4,7 GLS being independently associated with cardiovascular events, short‐ and long‐term hospital mortality, all‐cause death and hospitalization 1,5,14,17,18,21,31‐33 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies in hypertension have found that GCPS was signi cantly reduced in patients with hypertrophy [17,23]. Recent studies showed the negative effects of acute hyperglycemia on systolic LV global longitudinal strain and multilayer longitudinal and circumferential strain in asymptomatic T2DM and unfavorable subclinical reductions in global and average circumferential strain in obese adolescents with dysglycemia, which may indicate the importance of intensive blood glucose control [24,25]. Moreover, epicardial adipose tissue may be associated with LV structural and functional abnormalities and exercise intolerance in T2DM patients with asymptomatic heart failure [26], and serum levels of omentin-1 and Zinc-α2-glycoprotein have been recently de ned as the most important predictors for LV hypertrophy and LV diastolic dysfunction in T2DM patients [27].…”
Section: T2dm Aggravate LV Dysfunction In Hypertensionmentioning
confidence: 99%